The effect of land fragmentation on risk and technical efficiency of crop farms - Andreas Eder (Humboldt-Universität zu Berlin, DFG Research Unit 2569 FORLand "Agricultural Land Markets - Efficiency and Regulation", 2024)
Using a 2007-2014 panel of Austrian crop farms, we analyze the effect of multiple dimensions of land fragmentation on farms' production efficiency and risk performance. We use Data Envelopment Analysis (DEA), a non-parametric linear programming approach, to estimate efficiencies. Technical efficiency is decomposed into i) scale efficiency, ii) pure technical efficiency, and iii) input-mix efficiency. Risk efficiency, a concept borrowed from modern portfolio theory, measures the performance of a farm relative to a mean-variance frontier. A second-stage DEA analysis reveals that farms with fewer plots and a shorter average farmstead to plot distance tend to be more technically efficient. Larger plots allow for better exploitation of returns to scale. The scattering of plots has no statistically significant effect on technical efficiency but provides benefits in terms of higher risk efficiency. Land consolidation projects should carefully weigh the costs and benefits associated with different dimensions of land fragmentation.
urn:nbn:de:kobv:11-110-18452/29715-0
Keywords: Q12; Q15; Q18; 330; Land consolidation; Farmland fragmentation; Economies of scale; Agriculturalproductivity; Risk management; Data Envelopment Analysis